Checking the Functions Set in the form of Undisclosedly - Akhlimirzaev Akhmadjon; Mamadjanova Mamurakhon Kadirjanovna; Jakbarova Sarvinoz Abdinazirovna (International Journal on Integrated Education, 2022)
This paper introduces the concepts of the inverse function and focuses on one of the methods of constructing the equations of the points of intersection and asymototes of the graph of the inverse function with the coordinate axes.